Optimization Of Kri Maintenance in the Refurbishment Program to Support Improving the Readiness of Defense Equipment - Handoko , Yudi; Kurniawan, Eko Arie; Pardede, Richard Martogi (Journal of Industrial Engineering & Management Research, 2025)
This research examines the optimization of KRI (Republic of Indonesia Navy Ships) maintenance in the Refurbishment Program to support the readiness of defense equipment (Alutsista). The study aims to provide an overview and solutions to the challenges faced in the refurbishment program as an effort to accelerate the enhancement of Alutsista readiness, given the current aging condition of KRIs and budget constraints. The research is based on optimization theory, refurbishment theory, and defense equipment readiness theory. The study employs a descriptive qualitative method using tools Nvivo 12 and SWOT analysis, with data collected through interviews and literature reviews. The findings highlight several key issues in the refurbishment program, including frequent equipment damage, limited budget availability, ship automation and digitalization, declining performance of sensor and navigation systems, and human resource and technological constraints. While current human resources and supporting technology are capable of implementing refurbishment planning and execution, maintenance systems often fail to adhere to schedules due to hindering factors such as extensive coordination gaps, budget limitations, reliance on imported components, and technological restrictions. The study concludes that maintenance conditions, import dependency, and technological limitations in the refurbishment program can be addressed through improved coordination, adoption of new technologies, KRI identification, life cycle-based approaches, integration of technical efficiency, workforce optimization, and stakeholder synergy.